Preparation method and application of rock wool thermal insulation wool

By combining the modified silicon sol and modified adhesive with rock wool fibers to form rock wool fiber-silica wet gel composite material, and aging and modification treatment, the problems of high thermal conductivity, easy water absorption and insufficient weather resistance of rock wool insulation materials are solved, and better insulation, waterproof and weather resistance are achieved.

CN118515464BInactive Publication Date: 2025-03-21GUANG XI ZHONG BO XIN CAI LIAO KE JI JI TUAN YOU XIAN GONG SI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311351534.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

As a pipeline insulation material, rock wool has problems such as high thermal conductivity, easy water absorption and moisture absorption, and failure under corrosion of corrosive media, resulting in insufficient insulation, waterproofing and weather resistance.

Method used

By preparing a rock wool insulation wool, a modified silicon sol and a modified adhesive are used to combine with rock wool fibers to form a rock wool fiber-silica wet gel composite material, and through aging and modification treatment, its insulation, waterproofness and weather resistance are improved.

Benefits of technology

It significantly improves the insulation performance, waterproof performance and weather resistance of rock wool insulation, and can maintain long-term effectiveness in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005192603450000031
    Figure GDA0005192603450000031
  • Figure GDA0005192603450000121
    Figure GDA0005192603450000121
Patent Text Reader

Abstract

The invention discloses a preparation method and application of rock wool thermal insulation wool, which belongs to the technical field of thermal insulation materials, and comprises the following steps: step S1, preparing the following raw materials by weight: step S1, preparing the following raw materials by weight: 15-25 parts of rock wool fiber, 5-10 parts of modified silica sol, 20-60 parts of solid additive, 5-6 parts of modified adhesive, 40-50 parts of water glass, 45-85 parts of aging liquid, 60-70 parts of modified liquid, 75-85 parts of n-hexane; step S2, base material blending ; Step S3, impregnation; Step S4, aging; Step S5, modification; Step S6, preparation; In the present invention, modified adhesive and modified silica sol are added, and the modified adhesive contains rich active hydroxyl groups, benzene rings, trifluoromethyl groups, humic acid structures and unsaturated double bonds, which can not only participate in the curing reaction of the adhesive, but also react with the modified silica sol to improve the overall cross-linking density of the rock wool insulation wool coating, improve the waterproof performance of the rock wool insulation wool, and at the same time improve the weather resistance and thermal insulation performance of the rock wool insulation wool.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a preparation method and application of rock wool thermal insulation wool. Background Art

[0002] Rock wool is a man-made inorganic fiber made of selected basalt or diabase as the main raw material and a certain amount of supplementary materials through high-temperature melting and centrifugation. Because its production materials are non-toxic and pollution-free, and have good chemical stability and fire resistance, it has gradually been widely used in pipeline insulation systems.

[0003] However, because rock wool itself has a high thermal conductivity coefficient and, as a pipe insulation material, is in a complex environmental system, it is prone to absorbing moisture or becoming ineffective due to erosion by corrosive media during construction.

[0004] Therefore, providing a rock wool thermal insulation with good thermal insulation performance, waterproof performance and weather resistance is a technical problem that needs to be solved at present. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing rock wool thermal insulation wool to solve the problems raised in the background technology.

[0006] Another object of the present invention is to provide the application of the above rock wool insulation cotton as a pipeline insulation material in pipeline insulation.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing rock wool thermal insulation wool comprises the following steps:

[0009] Step S1, prepare the following raw materials in parts by weight: 15-25 parts of rock wool fiber, 5-10 parts of modified silica sol, 20-60 parts of solid additive, 5-6 parts of modified adhesive, 40-50 parts of water glass, 45-85 parts of aging liquid, 60-70 parts of modified liquid, and 75-85 parts of n-hexane;

[0010] Step S2, base material blending: the modified silica sol, the solid additive, the modified adhesive, the water glass and the photoinitiator are stirred uniformly in a vacuum state and protected from light to obtain a mixed solution;

[0011] Step S3, impregnation: under vacuum and light-proof conditions, pour 1 / 2 weight portion of the mixed solution into a culture dish, then slowly spread the rock wool fiber on the surface of the mixed solution, then pour the remaining weight portion of the mixed solution onto the surface of the rock wool fiber, so that the rock wool fiber is completely soaked in the mixed solution, and finally place the culture dish in a blast drying oven at 40-60° C. for 2-3 hours to condense the mixed solution into a wet gel, thereby obtaining a rock wool fiber-silicon dioxide wet gel composite material;

[0012] Step S4, aging: soaking the rock wool fiber-silicon dioxide wet gel composite material in step S3 in an aging solution prepared by mixing anhydrous ethanol and deionized water for 12-14 hours to obtain an aged rock wool fiber-silicon dioxide wet gel composite material, wherein the volume ratio of anhydrous ethanol to deionized water in the aging solution is 1:2-4;

[0013] Step S5, modification: immersing the aged rock wool fiber-silica wet gel composite material in a modification solution obtained by mixing anhydrous ethanol, trimethylchlorosilane and n-hexane, and modifying at 45-55° C. for 36-40 hours to obtain a modified rock wool fiber-silica wet gel composite material, wherein the volume ratio of anhydrous ethanol, trimethylchlorosilane and n-hexane in the modification solution is 5-10:4-6:8-10;

[0014] Step S6, preparation: soak the modified rock wool fiber-silicon dioxide wet gel composite material in n-hexane for 2 hours, then dry it at 70° C. for 12 hours, heat it to 200° C., and continue drying it for 3 hours to obtain rock wool insulation wool.

[0015] Furthermore, the rock wool fiber is the Jinwei brand rock wool fiber produced by Hebei Jinwei Energy Saving Technology Co., Ltd.

[0016] Furthermore, the solid additive is a mixture of nano-alumina and diatomaceous earth in a mass ratio of 1:1.5.

[0017] Furthermore, the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl benzophenone and benzophenone mixed in any ratio.

[0018] Further, the preparation method of the modified adhesive comprises the following steps:

[0019] Add the end-capping monomer, poly(1,4-butylene adipate), 2,2-dihydroxymethylbutyric acid and anhydrous DMF into a reflux reactor and introduce nitrogen to deoxygenate, stir and mix for 15-30 minutes, then add dibutyltin dilaurate, heat to 80-85°C for reaction for 1-3 hours, then add 1,4-butanediol and continue to react for 0.5-1 hour, then lower the temperature to 65-70°C, add the end-capping monomer again for end-capping reaction for 1-2 hours, lower the reaction temperature to 50-55°C, add triethylamine for neutralization reaction for 15-30 minutes, then add deionized water, and heat at 600°C. The mixture was emulsified at rpm for 0.5 h, and anhydrous DMF was removed by vacuum distillation to obtain a modified adhesive, wherein the amount ratio of the end-capping monomer, poly(1,4-butylene adipate), 2,2-dihydroxymethylbutyric acid, anhydrous DMF, dibutyltin dilaurate, 1,4-butanediol, triethylamine and deionized water added for the first time was 45-55 g: 25-35 g: 110-120 mL: 3-5 g: 0.15-0.25 mL: 1.8-3 mL: 2-4 mL: 100-110 mL, and the amount of the end-capping monomer added again was equal to the amount of the end-capping monomer added for the first time;

[0020] Furthermore, the method for preparing the end-capping monomer comprises the following steps:

[0021] Step A1, under nitrogen protection, add 4-trifluoromethylcinnamic acid to anhydrous DMF, stir evenly, then add N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and diethanolamine, raise the temperature to 65-75°C, stir and react for 4-6h, after the reaction is completed, filter, wash the filter cake with anhydrous ethanol and deionized water for 2-4 times, freeze-dry, and obtain fluorine-containing alcohol amide, wherein 4-trifluoromethylcinnamic acid, anhydrous DMF, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and diethanolamine are added, the temperature is raised to 65-75°C, and the reaction is stirred for 4-6h. The dosage ratio of diimine, 4-dimethylaminopyridine and diethanolamine is 35-45g:120-140mL:32-44mL:24-31g:16-22mL. In the above reaction process, anhydrous DMF is used as solvent, 4-dimethylaminopyridine is used as catalyst, N,N-dicyclohexylcarbodiimide is used as dehydrating agent, and the carboxyl group on 4-trifluoromethylcinnamic acid and the amino group on diethanolamine undergo amidation reaction to obtain fluorine-containing alcohol amide, the structural formula of which is as follows:

[0022]

[0023] Step A2, grind humic acid into powder and disperse it in anhydrous dichloromethane, add a mixture of fluorinated alcohol amide, p-toluenesulfonic acid and anhydrous DMF dropwise while stirring, and control the dripping to be completed within 30 minutes. After the dripping is completed, heat to 75-85°C, stir and react for 6-8 hours, filter after the reaction, rinse the filter residue with water until it is neutral, and dry for 4-6 hours to obtain a polycyclic ester, wherein the dosage ratio of humic acid, anhydrous dichloromethane and the mixture a is: 8-10g:65-75mL:120-160mL, in the mixed solution a, the amount ratio of the fluorinated alcohol amide, p-toluenesulfonic acid and anhydrous DMF is 35-45g:0.6-0.9g:120-160mL, in the above reaction process, in the above reaction process, with anhydrous dichloromethane as solvent and p-toluenesulfonic acid as catalyst, the hydroxyl group on the fluorinated alcohol amide and the carboxyl group on the humic acid undergo esterification reaction to obtain a polycondensed ring esterified product;

[0024] Step A3, adding isophorone diisocyanate, hydroquinone, dibutyltin dilaurate and acetone into a reaction kettle, stirring for 10-20 minutes, adding a polycyclic ester, stirring and reacting at 35°C for 4-6 hours, removing acetone by reduced pressure distillation, washing the distillation product with ether for 3-5 times, and drying for 16-24 hours to obtain a capping monomer, wherein the amount ratio of isophorone diisocyanate, hydroquinone, dibutyltin dilaurate, acetone and polycyclic ester is 46-52g:0.7-0.9g:0.38-0.42g:100-120mL:32-40g, so that the more active -NCO group in isophorone diisocyanate reacts with acetone and -OH of the polycyclic ester at low temperature to obtain a capping monomer containing -NCO, carbamate group and unsaturated double bond.

[0025] Furthermore, the preparation method of the modified silica sol comprises the following steps:

[0026] Step B1, add tetraethyl orthosilicate and anhydrous ethanol to a reaction kettle, heat to 30°C, add 10%wt hydrochloric acid solution while stirring to adjust the pH value to 4-5, react for 2h after the addition is completed, add modified carbon fiber and KH-560, heat to 50°C and stir to react for 4-6h, cool to room temperature, and obtain epoxidized silica sol, wherein the amount ratio of tetraethyl orthosilicate, anhydrous ethanol, modified carbon fiber and KH-560 is 14.6-17.6mL: 6.7-7.9mL: 3.5-4.5g: 11.5-12.5mL, and tetraethyl orthosilicate is used as a precursor, and hydrolysis and condensation reactions occur under acidic conditions to obtain epoxidized silica sol;

[0027] Step B2, heating the epoxidized silica sol to 40-45°C, adding tetrabutylammonium bromide, 3-mercaptopropionic acid and anhydrous ethanol mixed solution b dropwise while stirring, and after the addition is completed, heating to 110°C and stirring for 2-3h to obtain modified silica sol; wherein the amount ratio of the epoxidized silica sol to the mixed solution b is 15-25mL:50mL, and the amount ratio of tetrabutylammonium bromide, 3-mercaptopropionic acid and anhydrous ethanol in the mixed solution b is 0.45g:5mL:45mL, and under the action of tetrabutylammonium bromide, the carboxyl group of 3-mercaptopropionic acid undergoes a ring-opening reaction with the epoxy group to obtain the modified silica sol.

[0028] Furthermore, the preparation method of the modified carbon fiber comprises the following steps:

[0029] At room temperature, the carbon fiber is washed with anhydrous ethanol and deionized water for 2-4 times in sequence, dried at 90°C for 2-4h, cooled to room temperature, immersed in a 0.5wt% cobalt chloride aqueous solution for 3-5h, and then immersed in a 10wt% hydrogen peroxide aqueous solution for 5-7h, filtered, and dried at 120°C for 3-5h to obtain modified carbon fiber, wherein the amount ratio of carbon fiber, anhydrous ethanol, deionized water, 0.5wt% cobalt chloride aqueous solution and 10wt% hydrogen peroxide aqueous solution is 3-5g:5-10mL:5-10mL:20-30mL:25-35mL, the washed carbon fiber is activated by a rare earth aqueous solution, and then oxidized by hydrogen peroxide to obtain the modified carbon fiber, the number of oxygen-containing hydroxyl and carboxyl groups on the modified carbon fiber prepared by the above steps increases, and it can participate well in the subsequent reaction process.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] In order to improve the thermal insulation, weather resistance and waterproofness of rock wool thermal insulation, the present invention starts from two aspects. One is to add a modified adhesive. The modified adhesive contains rich active hydroxyl groups, benzene rings, trifluoromethyl groups, humic acid structures and unsaturated double bonds. On the one hand, the active hydroxyl groups can chemically react with isocyanate groups to improve the crosslinking degree of the modified adhesive system, strengthen the intermolecular binding force, and make it difficult for water molecules to enter the interior of the molecules through the coating film, thereby improving the thermal insulation and waterproof properties of the thermal insulation cotton. On the other hand, as an anchor point, the active hydroxyl groups react with the epoxy groups of the modified silica sol to further improve the crosslinking degree and the thermal insulation and waterproof properties of the rock wool thermal insulation. The trifluoromethyl group has a low surface energy and can improve the waterproofness and weather resistance of the modified adhesive. The structure of humic acid is highly rigid. When it is introduced into the modified adhesive, on the one hand, it synergizes with the rigid benzene ring structure to form a On the one hand, the thermal insulation performance of rock wool insulation is improved. On the other hand, humic acid-polyurethane block copolymer is formed in the modified adhesive, which makes the rock wool insulation have the waterproofness and weather resistance of humic acid. The presence of unsaturated double bonds enables the modified adhesive to chemically bond with the thiol in the modified silica sol under ultraviolet radiation, further improving the thermal insulation and waterproof properties of rock wool insulation. At the same time, the prepared modified adhesive itself is a polyester structure with good thermal insulation performance; secondly, the addition of modified silica sol, on the one hand, the low thermal conductivity of the silica aerogel structure is brought into play to improve the thermal insulation performance of the coating. On the other hand, the modified carbon fiber grafted on the surface of the modified silica sol has low thermal conductivity and good thermal insulation performance. Introducing it into the modified silica sol can work synergistically with the modified adhesive to jointly improve the thermal insulation, waterproofness and weather resistance of rock wool insulation. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] The rock wool fiber used in this application is the Jinwei brand rock wool fiber produced by Hebei Jinwei Energy Saving Technology Co., Ltd. The basic physical properties of the rock wool fiber are shown in Table 1 below:

[0034] Table 1

[0035] Flexural strength(MPa) Compressive strength(MPa) Elongation at break (%) Thermal conductivity (W / m·K) 0.37 0.37 0.39 0.038

[0036] Example 1

[0037] Preferably, the present embodiment provides a method for preparing modified carbon fiber, comprising the following steps:

[0038] At room temperature, 4 g of carbon fiber was washed three times with 7.5 mL of anhydrous ethanol and 7.5 mL of deionized water, dried at 90 ° C for 3 h, cooled to room temperature, immersed in 25 mL of 0.5 wt% cobalt chloride aqueous solution for 4 h, and then immersed in 30 mL of 10 wt% hydrogen peroxide aqueous solution for 7 h, filtered, and dried at 120 ° C for 4 h to obtain modified carbon fiber.

[0039] Example 2

[0040] Preferably, this embodiment provides a method for preparing a modified silica sol, comprising the following steps:

[0041] Step B1, add 16.1mL of tetraethyl orthosilicate and 7.3mL of anhydrous ethanol to a reaction kettle, heat to 30°C, add 10%wt hydrochloric acid solution dropwise while stirring to adjust the pH value to 4.5, react for 2h after the addition is complete, add 4.0g of modified carbon fiber prepared in Example 1 and 12mL of KH-560, heat to 50°C, stir and react for 5h, and cool to room temperature to obtain epoxidized silica sol;

[0042] Step B2, heat 20 mL of epoxidized silica sol to 42°C, add 0.45 g of tetrabutylammonium bromide, 5 mL of 3-mercaptopropionic acid and 45 mL of anhydrous ethanol mixed solution b dropwise while stirring; after the addition is completed, heat to 110°C and stir for 2.5 h to obtain modified silica sol.

[0043] Example 3

[0044] Preferably, the present embodiment provides a method for preparing an end-capping monomer, comprising the following steps:

[0045] Step A1, under nitrogen protection, add 40g 4-trifluoromethylcinnamic acid to 130mL anhydrous DMF, stir evenly, then add 38mL N,N-dicyclohexylcarbodiimide, 27.5g 4-dimethylaminopyridine and 19mL diethanolamine, heat to 70°C, stir and react for 5h, after the reaction is completed, filter, wash the filter cake with anhydrous ethanol and deionized water for 3 times respectively, freeze-dry to obtain fluorine-containing alcohol amide;

[0046] Step A2, grind 9g of humic acid into powder, and disperse it in 70mL of anhydrous dichloromethane, add a mixture of 40g of fluorine-containing alcohol amide, 0.75g of p-toluenesulfonic acid and 140mL of anhydrous DMF dropwise while stirring, and control the dripping to be completed within 30min. After the dripping is completed, heat to 80°C, stir and react for 7h. After the reaction is completed, filter, rinse the filter residue with water until it is neutral, and dry for 5h to obtain a polycondensed ring ester;

[0047] Step A3, add 49g of isophorone diisocyanate, 0.8g of hydroquinone, 0.40g of dibutyltin dilaurate and 110mL of acetone into a reactor, stir for 15min, add 36g of polycyclic ester, stir and react at 35°C for 35h, remove acetone by reduced pressure distillation, wash the distillation product with ether 4 times, and dry for 20h to obtain a capped monomer.

[0048] Example 4

[0049] Preferably, the present embodiment provides a method for preparing a modified adhesive, comprising the following steps:

[0050] 50 g of the end-capping monomer prepared in Example 3, 30 g of poly(1,4-butylene adipate), 4 g of 2,2-dihydroxymethylbutyric acid and 115 mL of anhydrous DMF were added to a reflux reactor, and nitrogen was introduced for deoxygenation. The mixture was stirred and mixed for 22 min, and then 0.20 mL of dibutyltin dilaurate was added. The mixture was heated to 83° C. and reacted for 2 h. 2.4 mL of 1,4-butanediol was added and the reaction was continued for 0.75 h. The temperature was then lowered to 68° C., and 50 g of the end-capping monomer prepared in Example 3 was added again for an end-capping reaction for 1.5 h. The reaction temperature was lowered to 53° C., 3 mL of triethylamine was added for a neutralization reaction for 23 min, and 105 mL of deionized water was added. The mixture was sheared and emulsified at 600 rpm for 0.5 h, and anhydrous DMF was removed by reduced pressure distillation to obtain a modified adhesive.

[0051] Example 5

[0052] This embodiment provides a method for preparing rock wool thermal insulation wool, comprising the following steps:

[0053] Step S1, prepare the following raw materials by weight: 15 parts of rock wool fiber, 5 parts of modified silica sol prepared in Example 2, 20 parts of solid additives, 5 parts of modified adhesive prepared in Example 4, 40 parts of water glass, 45 parts of aging liquid, 60-70 parts of modified liquid, and 75 parts of n-hexane, wherein the solid additive is a mixture of nano-alumina and diatomaceous earth in a mass ratio of 1:1.5;

[0054] Step S2, base material blending: the modified silica sol, the solid additive, the modified adhesive, the water glass and the photoinitiator are stirred uniformly in a vacuum state and protected from light to obtain a mixed solution;

[0055] Step S3, impregnation: under vacuum and light-proof conditions, pour 1 / 2 weight portion of the mixed solution into a culture dish, then slowly spread the rock wool fiber on the surface of the mixed solution, then pour the remaining weight portion of the mixed solution onto the surface of the rock wool fiber, so that the rock wool fiber is completely soaked in the mixed solution, and finally place the culture dish in a blast drying oven at 40° C. for 2 hours to condense the mixed solution into a wet gel, thereby obtaining a rock wool fiber-silicon dioxide wet gel composite material;

[0056] Step S4, aging: soaking the rock wool fiber-silicon dioxide wet gel composite material in step S3 in an aging solution prepared by mixing anhydrous ethanol and deionized water for 12 hours to obtain an aged rock wool fiber-silicon dioxide wet gel composite material, wherein the volume ratio of anhydrous ethanol to deionized water in the aging solution is 1:2;

[0057] Step S5, modification: immersing the aged rock wool fiber-silica wet gel composite material in a modification solution obtained by mixing anhydrous ethanol, trimethylchlorosilane and n-hexane, and modifying at 45° C. for 36 hours to obtain a modified rock wool fiber-silica wet gel composite material, wherein the volume ratio of anhydrous ethanol, trimethylchlorosilane and n-hexane in the modification solution is 5:4:8;

[0058] Step S6, preparation: soak the modified rock wool fiber-silicon dioxide wet gel composite material in n-hexane for 2 hours, then dry it at 70° C. for 12 hours, heat it to 200° C., and continue drying it for 3 hours to obtain rock wool insulation wool.

[0059] Example 6

[0060] This embodiment provides a method for preparing rock wool thermal insulation wool, comprising the following steps:

[0061] Step S1, preparing the following raw materials in parts by weight: 20 parts of rock wool fiber, 7.5 parts of modified silica sol, 40 parts of solid additive, 5.5 parts of modified adhesive, 45 parts of water glass, 65 parts of aging liquid, 65 parts of modified liquid, and 80 parts of n-hexane, wherein the solid additive is a mixture of nano-alumina and diatomaceous earth in a mass ratio of 1:1.5;

[0062] Step S2, base material blending: the modified silica sol, the solid additive, the modified adhesive, the water glass and the photoinitiator are stirred uniformly in a vacuum state and protected from light to obtain a mixed solution;

[0063] Step S3, impregnation: under vacuum and light-proof conditions, pour 1 / 2 weight portion of the mixed solution into a culture dish, then slowly spread the rock wool fiber on the surface of the mixed solution, then pour the remaining weight portion of the mixed solution onto the surface of the rock wool fiber, so that the rock wool fiber is completely soaked in the mixed solution, and finally place the culture dish in a blast dry coal box at 50° C. and let it stand for 2.5 hours to condense the mixed solution into a wet gel, thereby obtaining a rock wool fiber-silicon dioxide wet gel composite material;

[0064] Step S4, aging: soaking the rock wool fiber-silicon dioxide wet gel composite material in step S3 in an aging solution prepared by mixing anhydrous ethanol and deionized water for 12-14 hours to obtain an aged rock wool fiber-silicon dioxide wet gel composite material, wherein the volume ratio of anhydrous ethanol to deionized water in the aging solution is 1:3;

[0065] Step S5, modification: immersing the aged rock wool fiber-silica wet gel composite material in a modification solution obtained by mixing anhydrous ethanol, trimethylchlorosilane and n-hexane, and modifying at 45-55° C. for 38 hours to obtain a modified rock wool fiber-silica wet gel composite material, wherein the volume ratio of anhydrous ethanol, trimethylchlorosilane and n-hexane in the modification solution is 7.5:5:9;

[0066] Step S6, preparation: soak the modified rock wool fiber-silicon dioxide wet gel composite material in n-hexane for 2 hours, then dry it at 70° C. for 12 hours, heat it to 200° C., and continue drying it for 3 hours to obtain rock wool insulation wool.

[0067] Example 7

[0068] This embodiment provides a method for preparing rock wool thermal insulation wool, comprising the following steps:

[0069] Step S1, preparing the following raw materials by weight: 25 parts of rock wool fiber, 10 parts of modified silica sol, 60 parts of solid additive, 6 parts of modified adhesive, 50 parts of water glass, 85 parts of aging liquid, 70 parts of modified liquid, and 85 parts of n-hexane, wherein the solid additive is a mixture of nano-alumina and diatomaceous earth in a mass ratio of 1:1.5;

[0070] Step S2, base material blending: the modified silica sol, the solid additive, the modified adhesive, the water glass and the photoinitiator are stirred uniformly in a vacuum state and protected from light to obtain a mixed solution;

[0071] Step S3, impregnation: under vacuum and light-proof conditions, pour 1 / 2 weight portion of the mixed solution into a culture dish, then slowly spread the rock wool fiber on the surface of the mixed solution, then pour the remaining weight portion of the mixed solution onto the surface of the rock wool fiber, so that the rock wool fiber is completely soaked in the mixed solution, and finally place the culture dish in a blast dry coal box at 60° C. and let it stand for 3 hours to condense the mixed solution into a wet gel, thereby obtaining a rock wool fiber-silicon dioxide wet gel composite material;

[0072] Step S4, aging: soaking the rock wool fiber-silicon dioxide wet gel composite material in step S3 in an aging solution prepared by mixing anhydrous ethanol and deionized water for 14 hours to obtain an aged rock wool fiber-silicon dioxide wet gel composite material, wherein the volume ratio of anhydrous ethanol to deionized water in the aging solution is 1:4;

[0073] Step S5, modification: immersing the aged rock wool fiber-silica wet gel composite material in a modification solution obtained by mixing anhydrous ethanol, trimethylchlorosilane and n-hexane, and modifying at 55° C. for 40 hours to obtain a modified rock wool fiber-silica wet gel composite material, wherein the volume ratio of anhydrous ethanol, trimethylchlorosilane and n-hexane in the modification solution is 10:6:10;

[0074] Step S6, preparation: soak the modified rock wool fiber-silicon dioxide wet gel composite material in n-hexane for 2 hours, then dry it at 70° C. for 12 hours, heat it to 200° C., and continue drying it for 3 hours to obtain rock wool insulation wool.

[0075] Comparative Example 1

[0076] The modified carbon fiber in Example 2 was removed, and the prepared material was used to replace the modified silica sol in Example 6, and the other raw materials and preparation process remained unchanged.

[0077] Comparative Example 2

[0078] The 3-mercaptopropionic acid in Example 2 was replaced by propionic acid, and the prepared substance was used to replace the modified silica sol in Example 6, and the other raw materials and preparation process remained unchanged.

[0079] Comparative Example 3

[0080] The 4-trifluoromethylcinnamic acid in Example 3 was removed, and the prepared substance was used to replace the end-capping monomer in Example 4, and the other raw materials and preparation process remained unchanged. The prepared substance was used to replace the modified adhesive in Example 6, and the other raw materials and preparation process remained unchanged.

[0081] Comparative Example 4

[0082] The humic acid in Example 3 was removed, and the prepared substance was used to replace the end-capping monomer in Example 4, and the other raw materials and preparation process remained unchanged. The prepared substance was used to replace the modified adhesive in Example 6, and the other raw materials and preparation process remained unchanged.

[0083] Comparative Example 5

[0084] The end-capping monomer in Example 4 was replaced by isophorone diisocyanate, and the other raw materials and preparation process remained unchanged. The prepared substance was then used to replace the modified adhesive in Example 6, and the other raw materials and preparation process remained unchanged.

[0085] Comparative Example 6

[0086] The modified adhesive in Example 6 was removed, and the other raw materials and preparation process remained unchanged.

[0087] Comparative Example 7

[0088] The modified silica sol in Example 6 was removed, and the other raw materials and preparation process remained unchanged.

[0089] Performance Testing

[0090] Referring to the "Industrial Equipment and Pipeline Insulation Engineering Construction and Acceptance Code" (GB / T 50185-2019), the rock wool insulation wool prepared in Examples 5-7 and Comparative Examples 1-7 was used for pipeline insulation by bundling method, and the following properties were tested:

[0091] The compressive strength test is carried out in accordance with the "Test Methods for Inorganic Rigid Insulation Products" (GB / T5486-2008); the thermal conductivity test of the insulation board is carried out in accordance with the "Guarded Hot Plate Method for Determination of Steady-State Thermal Resistance and Related Properties of Insulation Materials" (GB / T10294); the water repellency test of the insulation cotton is carried out in accordance with the "Test Method for Water Repellency of Insulation Materials" (GB / T10299), and the weather resistance of the insulation cotton is carried out in accordance with GB / T 30808. The specific test results are shown in Table 2 below:

[0092] Table 2

[0093]

[0094] It can be seen from Table 2 that compared with comparative examples 1-7, the thermal conductivity of the rock wool thermal insulation wool prepared in Examples 4-6 is small, and the hydrophobicity is small, and it still has a high tensile strength after being soaked in acid solution and alkaline solution. Therefore, the rock wool thermal insulation wool prepared by the present invention has excellent thermal insulation, waterproofness and weather resistance.

[0095] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing rock wool thermal insulation wool, characterized in that: The following steps are involved: Step S1, prepare the following raw materials in parts by weight: 15-25 parts of rock wool fiber, 5-10 parts of modified silica sol, 20-60 parts of solid additive, 5-6 parts of modified adhesive, 40-50 parts of water glass, 45-85 parts of aging liquid, 60-70 parts of modified liquid, and 75-85 parts of n-hexane; The solid additive is a mixture of nano-alumina and diatomaceous earth in a mass ratio of 1:1.5; Step S2, stirring the modified silica sol, the solid additive, the modified adhesive, the water glass and the photoinitiator in a vacuum and light-proof state to obtain a mixed solution; Step S3, under vacuum and light-proof conditions, pour 1 / 2 weight portion of the mixed solution into a culture dish, then slowly spread the rock wool fiber on the surface of the mixed solution, then pour the remaining weight portion of the mixed solution onto the surface of the rock wool fiber, so that the rock wool fiber is completely soaked in the mixed solution, and finally place the culture dish in a blast drying oven at 40-60° C. for 2-3 hours to condense the mixed solution into a wet gel, thereby obtaining a rock wool fiber-silicon dioxide wet gel composite material; Step S4, soaking the rock wool fiber-silicon dioxide wet gel composite material in step S3 in an aging solution prepared by mixing anhydrous ethanol and deionized water for 12-14 hours to obtain an aged rock wool fiber-silicon dioxide wet gel composite material, wherein the volume ratio of anhydrous ethanol to deionized water in the aging solution is 1:2-4; Step S5, immersing the aged rock wool fiber-silica wet gel composite material in a modification solution obtained by mixing anhydrous ethanol, trimethylchlorosilane and n-hexane, and modifying at 45-55° C. for 36-40 hours to obtain a modified rock wool fiber-silica wet gel composite material, wherein the volume ratio of anhydrous ethanol, trimethylchlorosilane and n-hexane in the modification solution is 5-10:4-6:8-10; Step S6, soaking the modified rock wool fiber-silicon dioxide wet gel composite material in n-hexane for 2 hours, then drying at 70° C. for 12 hours, heating to 200° C., and continuing to dry for 3 hours to obtain rock wool insulation wool; The preparation method of the modified adhesive comprises the following steps: adding an end-capping monomer, poly(1,4-butylene adipate), 2,2-dihydroxymethylbutyric acid and anhydrous DMF into a reflux reactor and introducing nitrogen for deoxygenation, stirring and mixing for 15-30 minutes, then adding dibutyltin dilaurate, heating to 80-85° C. for reaction for 1-3 hours, then adding 1,4-butanediol for further reaction for 0.5-1 hour, then lowering the temperature to 65-70° C., adding the end-capping monomer again for an end-capping reaction for 1-2 hours, lowering the reaction temperature to 50-55° C., adding triethylamine for neutralization reaction for 15-30 minutes, then adding deionized water, shearing and emulsifying at 600 rpm for 0.5 hours, and removing the anhydrous DMF by reduced pressure distillation to obtain a modified adhesive; wherein the amount of the end-capping monomer added again is equal to the amount of the end-capping monomer added for the first time; The method for preparing the end-capping monomer comprises the following steps: Step A1, under nitrogen protection, add 4-trifluoromethylcinnamic acid to anhydrous DMF, stir evenly, then add N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and diethanolamine, raise the temperature to 65-75°C, stir and react for 4-6 hours, after the reaction is completed, filter, wash the filter cake with anhydrous ethanol and deionized water for 2-4 times respectively, and freeze-dry to obtain fluorine-containing alcohol amide; Step A2, grinding humic acid into powder and dispersing it in anhydrous dichloromethane, adding a mixed solution a of fluorinated alcohol amide, p-toluenesulfonic acid and anhydrous DMF dropwise while stirring, and controlling the dropping to be completed within 30 minutes. After the dropping is completed, the temperature is raised to 75-85° C., and the reaction is stirred for 6-8 hours. After the reaction is completed, the filter is suctioned, and the filter residue is washed with water until it is neutral, and dried for 4-6 hours to obtain a polycondensed ring ester; Step A3, adding isophorone diisocyanate, hydroquinone, dibutyltin dilaurate and acetone into a reaction kettle, stirring for 10-20 minutes, adding polycyclic ester, stirring and reacting at 35° C. for 4-6 hours, removing acetone by reduced pressure distillation, washing the distillation product with ether for 3-5 times, and drying for 16-24 hours to obtain a capped monomer; The preparation method of the modified silica sol comprises the following steps: Step B1, add tetraethyl orthosilicate and anhydrous ethanol to a reaction kettle, heat to 30°C, add 10%wt hydrochloric acid solution dropwise while stirring to adjust the pH value to 4-5, react for 2h after the addition is complete, add modified carbon fiber and KH-560, heat to 50°C, stir and react for 4-6h, and cool to room temperature to obtain epoxidized silica sol; Step B2, heating the epoxidized silica sol to 40-45° C., adding tetrabutylammonium bromide, 3-mercaptopropionic acid and anhydrous ethanol mixed solution b dropwise while stirring, and after the addition is completed, heating to 110° C. and stirring for 2-3 hours to obtain a modified silica sol; The modified carbon fiber is prepared by washing the carbon fiber with alcohol and water for multiple times, activating it with a cobalt chloride aqueous solution and oxidizing it with a hydrogen peroxide aqueous solution.

2. The method for preparing rock wool thermal insulation wool according to claim 1, characterized in that: The method for preparing the modified carbon fiber comprises the following steps: At room temperature, the carbon fiber was washed with anhydrous ethanol and deionized water for 2-4 times in sequence, dried at 90°C for 2-4 hours, cooled to room temperature, immersed in a 0.5wt% cobalt chloride aqueous solution for 3-5 hours, then immersed in a 10wt% hydrogen peroxide aqueous solution for 5-7 hours, filtered, and dried at 120°C for 3-5 hours to obtain modified carbon fiber.

3. The method for preparing rock wool thermal insulation wool according to claim 1, characterized in that: The amount ratio of the end-capping monomer, poly(1,4-butylene adipate), 2,2-dihydroxymethylbutyric acid, anhydrous DMF, dibutyltin dilaurate, 1,4-butanediol, triethylamine and deionized water added for the first time is 45-55g: 25-35g: 110-120mL: 3-5g: 0.15-0.25mL: 1.8-3mL: 2-4mL: 100-110mL, and the amount of the end-capping monomer added again is equal to the amount of the end-capping monomer added for the first time.

4. The method for preparing rock wool thermal insulation wool according to claim 1, characterized in that: In the step A1, the usage ratio of 4-trifluoromethylcinnamic acid, anhydrous DMF, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and diethanolamine is 35-45 g: 120-140 mL: 32-44 mL: 24-31 g: 16-22 mL, and in the step A2, the usage ratio of humic acid, anhydrous dichloromethane and mixed solution a is 8-10 g: 65-75 mL: 120-160 mL. L, in the mixed solution a, the usage ratio of the fluorinated alcohol amide, p-toluenesulfonic acid and anhydrous DMF is 35-45 g: 0.6-0.9 g: 120-160 mL, and in the step A3, the usage ratio of isophorone diisocyanate, hydroquinone, dibutyltin dilaurate, acetone and polycondensed ring ester is 46-52 g: 0.7-0.9 g: 0.38-0.42 g: 100-120 mL: 32-40 g.

5. The method for preparing rock wool thermal insulation wool according to claim 1, characterized in that: In the step B1, the usage ratio of tetraethyl orthosilicate, anhydrous ethanol, modified carbon fiber and KH-560 is 14.6-17.6 mL: 6.7-7.9 mL: 3.5-4.5 g: 11.5-12.5 mL.

6. The method for preparing rock wool thermal insulation wool according to claim 1, characterized in that: In the step B2, the usage ratio of the epoxide silica sol and the mixed solution b is 15-25 mL:50 mL, and in the mixed solution b, the usage ratio of tetrabutylammonium bromide, 3-mercaptopropionic acid and anhydrous ethanol is 0.45 g:5 mL:45 mL.

7. The method for preparing rock wool thermal insulation wool according to claim 2, characterized in that: The usage ratio of the carbon fiber, anhydrous ethanol, deionized water, 0.5wt% cobalt chloride aqueous solution and 10wt% hydrogen peroxide aqueous solution is 3-5g:5-10mL:5-10mL:20-30mL:25-35mL.

8. Use of rock wool thermal insulation wool prepared by the method for preparing rock wool thermal insulation wool according to any one of claims 1 to 7 in pipe thermal insulation.

Citation Information

Patent Citations

  • Method for preparing silica aerogel composite material by adopting chloride-free and alcohol-free process

    CN108314411A

  • Preparing method of glass-wool-based compound sound absorbing material

    CN109135261A